Governing the internet in the privacy arena - Carsten Ochs; Fabian Pittroff; Barbara Büttner; Jörn Lamla (Internet Policy Review)
The surveillance disclosures triggered by Snowden have fueled the public re-negotiation of privacy. To follow resulting controversies we present a methodology that links social worlds theory to approaches asking for the democratic governance character of issue-centred arenas. After having outlined this approach it is put to the test. We analyse and compare two cases: the Schengen/National Routing, and the Parliamentary Committee investigating the NSA surveillance disclosures. The analysis reveals two oscillating governance modes at work in the privacy arena; their interplay results in an obstruction. Based on this observation we finally provide a diagnosis of possible future arena trajectories.